Prevalence and risk factors associated with common mental disorders among medical students - Amine Selim de Salles Gonçalves Melado; Filipe Alvarenga Caetano Vitorino; Ana Rosa Murad Szpilman; Wanêssa Lacerda Poton (Sociedade Brasileira de Medicina de Família e Comunidade, 2019)
Objective: To identify the prevalence of common mental disorders (CMD) in medical students at Vila Velha University (UVV), ES, and its associated factors. Methods: A cross-sectional study was conducted with 360 medical students from February to April 2018. A self-administered, confidential and online questionnaire was used, including sociodemographic, economic data, family support, friends' network, physical activity and academic performance, as well as Self-Reporting Questionnaire (SRQ-20). Statistical analysis was performed using the STATA program, version 13.0. The Ethics Committee on Research with Humans approved the study, under number 2.108.290. Results: The prevalence of CMD among students was 45.6%. Risk factors were mental disorder in the family (RR 1.24, 95% CI 1.01-1.54), poor sleep quality (RR 1.49, 95% CI 1.17-1.90), fear that impaired the academic result (RR 1.33, 95% CI 1.01-1.77), feeling rejected by friends (RR 1.45, 95% CI 1.07-1.96), thinking about giving up the course (RR 1.67, 95% CI 1.29-2.17) and physical discomfort during the test (RR 1.63, 95% CI, 1.21-2.20). Conclusions: The overall prevalence of CMD among students was high, and the risk factors were significant. It is recommended that educational institutions and responsible government agencies be able to formulate and subsidize preventive actions and care for the mental health of medical students.